Wandering eyes: Eye movements during mind wandering in video lectures - Zhang, Han; Miller, Kevin F.; Sun, Xin; Cortina, Kai S. (Applied cognitive psychology, 2020)
Summary Video lectures are increasingly prevalent, but they present challenges to learners. Students' minds often wander, yet we know little about how mind wandering affects attention during video lectures. This paper presents two studies that examined eye movement patterns of mind wandering during video lectures. In the studies, mind wandering reports were collected by either self‐caught reports or thought probes. Results were similar across the studies: mind wandering was associated with an increased allocation of fixations to the instructor's image. For fixations on the slides, the average duration increased but the dispersion decreased. Moreover, preliminary evidence suggested that fixation duration and dispersion can diminish soon after self‐caught reports of mind wandering. Overall, these findings help advance our understanding of how learners' attention is affected during mind wandering and may facilitate efforts in objectively identifying mind wandering. Future research is needed to determine if these findings can extend to other instructional formats.